Randomized double-blind cross-over study of iohexol and Amipaque in cerebral angiography. - Amundsen, P; Dugstad, G; Presthus, J; Sveen, K (American Journal of Neuroradiology, 1983)
Iohexol was compared with Amipaque (metrizamide) in a double-blind study in one pair of injections in each of 20 patients referred for routine cerebral angiography. Catheter position, patient position, injection pressure, contrast medium volume, and concentration (300 mg l/ml) were the same in the two injections, with iohexol and Amipaque being used alternately. Except for these two injections iohexol was used throughout. The parameters studied included diagnostic information obtained (quality of the examination), circulation time, and comparison of patient reactions to the pair of injections (e.g., electrocardiogram, heart rate, and subjective reactions). The patients' reactions to the noncomparative part of the examination were evaluated also, and the patients were observed for possible adverse reactions after the examination. No difference could be detected between the two contrast media in this series. No serious adverse reactions occurred.